Analisis Intellectual Capital dan Kinerja Keuangan Perbankan (Pendekatan Dinamis pada Panel Data) - Ghozali Maski (Jurnal Aplikasi Manajemen, 2010)
The performance of economic entities has been a research matter even in the ancient world. The human genius has been recognized as a vehicle for certain valueable capabilities and as the critical enabler of trnasforming processes. But it has not been considered as an intellectual capitalizator or intellectual asset. The field for intellectual capital and the related philosophy of knowledge management has a risen recently to an interesting research object world wide. Applies the Value Added Intellectual Coefficient method and Rate of Growth Intellectual Capital in order to analyze the dynamic effect of Indonesia commercail banks for the financial period 2005 quarter 1 untill 2008 quarter 4. Focuses in bnaking financial performance both for current period and the future. The research method is quantitative analysis and the sample size there are 22 banks by using purposive sampling method. The method of estimation is dynamic model on panel data. The result of the study are, as a whole all banks have relatively smaller capital employed efficiency than human and structural efficiencies. The long term effect has greater impact for Return on Asset and Solvency Ratio compare to the short term one. Average response time required for adjustment of Return on Asset is faster then Solvency Ratio.Key words: Value Added Intellectual Coefficient, Rate of Growth Intellectual Capital, Return on Asset, and Solvency Ratio